LEARNING MEDIA DEVELOPMENT APPROACH WITH A RECTANGLE PROBLEM POSING BASED GEOGEBRA - Bagus Ardi Saputro (IKIP Siliwangi and I-MES, 2016)
This study aims to develop learning media quadrilateral with problem posing approach based GeoGebra. 8 teachers from three different schools have stated that this media can be used to teach the nature - the nature of the quadrilateral. After the learning is done using this media, this media can facilitate students in asking about the nature - the nature of wake quadrilateral, facilitating students to learn the relationship between the type - the type of wake rectangles that have the same properties, and provides the opportunity for teachers in the evaluation of mathematical communication current students ask and write.